Cranial index of ancient pre-columbian peruvian population with artificial cephalic deformation - Gálvez-Calla, Luis (2015)
Objective: The study is to point out the cranial shape determined by the cranial index in relation with the causal agent, the cultural area of skulls origin and cranial morphological trends visually obtained. Methodology: it was used, 18 pre-columbian skulls included in the typological classification of Peter Weiss, in which we proceeded to measure the width and anteroposterior interparietal maximum length, measured from the glabella to opistocráneo; using the mathematical formula that multiplies the eu-eu by 100, divided by the length gl-op. Cranial indexes and cranial shapes are related to the causative agent, the cultural area of origin of the skulls and dolichocephalic and brachycephalic visual trends established in a previous study, seeking equivalence with cranial forms considered in the classification of Martin and Broca. Results and conclusions: 1. The pre-columbian peruvian skulls from the coastal cultural area with artificial deformation by “cuna” presented brachycephalic forms according to Martin with a cranial index average of 97.0, consistent with the visual perception of the cranial shape. 2. The pre-columbian peruvian andean cultural area skulls with artificial cephalic deformation “llautu” have dolichocephalous forms according to Martin averaging 73.1 cranial index consistent with the visual perception of the cranial shape. 3. The cranial forms determined by cranial index are consistent with cranial forms visually obtained by a higher standard. The discrepancies observed may be due to applying the semi rigids artifacts that compressed opistocraneo and possibly allowed compensatory longitudinal expansion of the skull at the expense of lambda.